Implementation of the Principle of Accountability in the name Transfer Procedure of Property Rights Certificate at the Land Office Jayapura District - Solossa, Marthinus; Pondayar, Yustus; Tanati, Daniel; Palenewen, James Yoseph (Journal of Progressive Law and Legal Studies, 2023)
To ensure legal certainty, it is important to fulfill obligations during the process of changing the name on the title certificate at the Jayapura Regency Land Office. The aim of this research is to determine the application of the principle of Accountability in the process of changing the name of a property rights certificate at the Jayapura Regency Land Office and to identify the variables that cause this process to encounter obstacles. The research approach used is normative, meaning it refers to secondary legal materials such as books, articles, written regulations and other legal documents. The findings of this research indicate that the Jayapura Regency Land Office, in accordance with the Republic of Indonesia PERKABAN, has implemented the principle of accountability fully and correctly in the process of submitting title transfers for land ownership certificates. There are 2 (two) obstacles, both internal and external, in implementing land ownership rights at the Jayapura Regency Land Office. Internal obstacles include a lack of human resources and the large volume of applications that have been submitted to the Jayapura Regency Land Office. Meanwhile there are external challenges, such as the large number of heirs and tax arrears.